ISLAMIC ACTIVISM AND WOMEN'S EMPOWERMENT: A STUDY ON THE FATAYAT WOMEN'S EMPOWERMENT MOVEMENT IN THE SPECIAL REGION OF YOGYAKARTA - Khoniq Nur Afiah; Ayna Jamila Salsabila (International Conference on Social and Islamic Studies, 2021)
This article discusses a women's movement as Islamic activism as well as a women's empowerment movement. Fatayat DIY as a women's organization under the auspices of Nahdlatul Ulama is a manifestation of women's Islamic activism. In addition, Fatayat NU DIY as a manifestation of women's Islamic activism also creates a concrete movement in the form of empowering women as a big agenda in organizing community welfare, especially for women. This research is field research focused on studying an organization called Fatayat NU DIY. The research method used in this study is a qualitative-descriptive with sociological approach. This study uses a keen analysis of new social movement theory as a tool to observe further about the phenomenon of the women's movement as Islamic activism and women's empowerment movement. The results of the study states that: first, Fatayat NU DIY is a portrait of the form in women's Islamic activism precisely this era. Fatayat NU DIY as women's Islamic activism at this moment is a forum for women to actualize bright ideas and other potentials possessed by women. Second, Fatayat DIY NU does not only sign in the area of ​​Islamic women's activism, but enters the area of ​​women's empowerment. Fatayat NU DIY as women's Islamic activism paved the way and awareness of the pivotal empowering of fellow women as well as providing welfare for the community, especially for women. The form of empowerment conducted by Fatayat NU DIY in empowering women is proven by the existence of: the establishment of the LKP3A Institution, the establishment of the BLKK PW NU DIY, Acting as Intermediary Actor, and settled women as a source of knowledge.